2018
DOI: 10.1111/jabr.12117
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in ER nurses: Review of the literature and interview themes

Abstract: Burnout is especially disruptive among emergency room (ER) nurses. This report covers the influencing factors and outcomes related to burnout in ER nursing populations, with the goal of providing helpful information to a professional audience. The present article includes a literature review on burnout as it occurs in the ER. Interviews from a small sample of ER nurses (n = 5) are analyzed through a combination of deductive thematic analysis and computerized text analysis. Research from various related fields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…According to the Webster Encyclopedic Unabridged Dictionary of the English Language (cited by Figley) [ 17 ], empathy fatigue is “a feeling of deep empathy and sorrow for someone who is suffering”. The difference between a healthy professional who works with human suffering and one who has the syndrome is not that both do not suffer the symptoms of empathic burnout, but rather the chronic nature of the symptoms, as pointed out in recent literature reviews [ 18 , 19 , 20 , 21 ]. Although it is a concept that was born several years ago in Spain, its meaning has been poorly studied and is often confused with other terms, including the much more studied burnout syndrome [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Webster Encyclopedic Unabridged Dictionary of the English Language (cited by Figley) [ 17 ], empathy fatigue is “a feeling of deep empathy and sorrow for someone who is suffering”. The difference between a healthy professional who works with human suffering and one who has the syndrome is not that both do not suffer the symptoms of empathic burnout, but rather the chronic nature of the symptoms, as pointed out in recent literature reviews [ 18 , 19 , 20 , 21 ]. Although it is a concept that was born several years ago in Spain, its meaning has been poorly studied and is often confused with other terms, including the much more studied burnout syndrome [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Job burnout among nursing staff is about 13% to 27%, which is significantly higher than the general population due to the intense nature of occupational duties and high level of stress (3, 4). Interestingly, the insufficient number of nurses and the resulting high workload is the first source of exhaustion (1).…”
Section: Introductionmentioning
confidence: 99%
“…As a follow‐up of the earlier more extensive review by Abellanoza, Haas, and Gatchel () and Buse () has also indicated that burnout in medicine is a result of high demand on the one hand, and low support/resources on the other hand. Relatedly, Harrison et al.…”
Section: Other Related Studiesmentioning
confidence: 90%